Internalization of Falsafah Peri Mestike Gayo as an Effort To Developing Students Characters Based on Local Authority In SMA 1 Takengon Aceh Central District - Indra, Indra; Rasyidin, Al; Sukiman, Sukiman (International Journal for Educational and Vocational Studies, 2019)
At present, there are two trending topic studies in the world of education that are hotly discussed, namely character education and local wisdom (indigenization). "Urang Gayo" is one of the ethnic groups in Indonesia that is rich in the noble values of Adat and its culture, until now they are still holding fast to defend it, because they believe that the customs and culture of Gayo can guide them in creating harmonization in the community, forming or fostering character, and does not conflict with the values of Islamic teachings. The internalization of Peri Mestike in education is part of efforts to foster character and as an effort to preserve the values of indigenous wisdom and culture of Gayo. The purpose of this study is to determine the importance of the internalization of the "Peri Mestike" (PM) Gayo philosophy in fostering the character of students, as well as the internalization process. The method used is a qualitative method with the ethnopedagogic approach, the data conclusions using the interview method with the strategy of "Swelling Gengku", (the method of imagery and class). This study shows that education must synergize with local wisdom in fostering the character of students because the culture is their identity. The results showed the importance of PM in internalizing and integrating with education as local wisdom and in schools, as for the process found first; through understanding PM by presenting qualified figures, second; with integration in learning material, third; through extracurricular activities, photos or posters that read PM sentences. Furthermore, the school through the principal's policy will continue to try to formulate with the teachers so that the PM can be a subject of local content.